solve by completing square:

x2 - (root2 + 1)x + root 2=0

x2 - ( root2 + 1)x + root2= 0

= x2 - 2. (1/2) . (root2 + 1). x + {(root2 + 1)/2}2 - (root2 + 1)2/4 + root2= 0

= {x - (root2 + 1)/2}2 = (root2+ 1)2/4 - root2 = ( 2 + 1 + 2root2)/4 - root2 = 3 -2root2/4= (root2 - 1)2/4

= x - (root2 + 1)/2= +(root2-1)/2 , or , -(root2 - 1)/2

= x = root2 , or, 1

ANS= x = root2 or 1.

  • -13

i didn't understand :-/

  • -18
x2-(root2+1)x+root2=0
x2-root2x-x+root2=0
x(x-1)-1 (x-root2)
(x-1) (x-root2)
x=1     x=root2 

This is done by the method of splitting the middle term ....
  • 16
COULD NOT UNDERSTAND!!!
 
  • -22
x=√2 or 1 The derived answer with steps is explained in the image

  • 83
This answer can be more easier it's quite confusing so u should provide the photography of splitting one not of coMplete square method
  • -8
By middle term splitting

  • 10
Root2 or 1
  • -3
????
  • -3
same as pranav
  • -5
By factorisation method!

  • 3
x square -(root 2+1)x+ root 2 Is very important sum Is this sum is useful or not Thanks you

  • 1
Unhelpful
  • 0
What are you looking for?